GSM-enabled Wireless Patient Monitoring System Integrating Microcontroller for Managing Vital Signstal signs - Ali, Tariq Emad; Ali, Faten Imad; TEJFEL, Máté; Zoltán, Alwahab Dhulfiqar (Al-Khwarizmi Engineering Journal, 2024)
The primary focus of this project is developing a cutting-edge remote monitoring of patients device for use in an intensive care unit (ICU). The gadget is designed to capture and transmit vital health data from the patient's body, including oxygen saturation levels, heart rate, and temperatures. It is also capable of monitoring a pacemaker. Information is then sent to a remote location after that. The suggested system receives the patient's vital signs and uses them as input on a computer in the nursing room. This transmission is made possible via a transmitter-receiver system consisting of two Arduino kits connected to Bluetooth devices. If any anomalous numbers are discovered as the data is processed, the computer notifies the doctor via the Global System for Mobile Communications (GSM) and the doctor's mobile device. The primary objective of this device is to enable remote monitoring of a patient's medical parameters and prompt alerting of doctors who are situated in remote places of any concerning circumstances. The doctor's mobile device receives the collected values from the workstation. The entire system's structure is implemented using the Visual Basic programming dialect.